2020
DOI: 10.3390/pharmaceutics12100978
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Lymphatic Delivery of Methotrexate Using W/O/W Nanoemulsion: In Vitro Characterization and Pharmacokinetic Study

Abstract: Methotrexate, which is widely used in the treatment of cancer and immune-related diseases, has limitations in use because of its low bioavailability, short half-life, and tissue toxicity. Thus, in this study, a nano-sized water-in-oil-in-water (W/O/W) double emulsion containing methotrexate was prepared to enhance its lymphatic delivery and bioavailability. Based on the results from solubility testing and a pseudo-ternary diagram study, olive oil as the oil, Labrasol as a surfactant, and ethanol as a co-surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 51 publications
(71 reference statements)
1
28
0
Order By: Relevance
“…Previous formulation studies have aimed to identify and compare differences in pharmacokinetics between free methotrexate solution and methotrexate-loaded nanoformulation administration groups [ 6 , 7 ]. These were pharmacokinetic studies on methotrexate-loaded nanoparticles [poly(lactic-co-glycolic acid)] and nanoemulsion formulations (olive oil and Labrasol), as well as free methotrexate solution as a control.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous formulation studies have aimed to identify and compare differences in pharmacokinetics between free methotrexate solution and methotrexate-loaded nanoformulation administration groups [ 6 , 7 ]. These were pharmacokinetic studies on methotrexate-loaded nanoparticles [poly(lactic-co-glycolic acid)] and nanoemulsion formulations (olive oil and Labrasol), as well as free methotrexate solution as a control.…”
Section: Methodsmentioning
confidence: 99%
“…Research into changes in the pharmacokinetic properties of nano-sized formulations of various drugs is actively being conducted [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. Most nanoformulation studies have reported that the bioavailability of nanoformulated drugs is largely improved and delayed-release patterns are observed in comparison to the standard drugs used as controls [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. These results clearly imply that changes of in vivo pharmacokinetics are associated with the nanoformulation of the drug.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of them are already approved for parenteral use, e.g., Labrafac ® WL 1349, Miglyol ® 812, Lipoid ® E PC, Lipoid ® S 100, Kollisolv ® PEG 400, Kolliphor ® HS15, Kolliphor ® EL, Kollisolv ® PG, and Tween ® 80 [34]. Among the excipients not approved for IV route, the three macrogolglycerides are recommended for oral, topical, or vaginal routes, but given their interesting properties, they are reported in several formulation assays for IV administration [35][36][37]. Transcutol ® HP is approved by the FDA for topical and transdermal routes, and besides, the manufacturer recommends its use for parenteral route.…”
Section: In Vitro Haemolysis Assaymentioning
confidence: 99%